THE EFFECTS OF SOLUTION CHEMISTRY ON THE STICKING EFFICIENCIES OF VIABLE ENTEROCOCCUS FAECALIS: AN ATOMIC FORCE MICROSCOPY AND MODELING STUDY - Cail T.L.; Hochella Jr.M.F. (My University, 2005)
Atomic force microscopy (AFM) and Derjaguin-Landau-Verwey-Overbeek (DLVO) theory in combination with the interaction force boundary layer (IFBL) model have been used to empirically and theoretically calculate sticking efficiencies (α) of Enterococcus faecalis cells against a silica glass surface. Sticking efficiencies were calculated in solutions of varying pH and ionic strength and related to maximum distances of transport through a hypothetical soil block using colloid filtration theory. AFM measurements show that the repulsive and attractive forces between E. faecalis cells and a glass surface are a function of ionic strength but are less sensitive to changes in solution pH. Zeta (ζ)-potential measurements of the cells and glass surfaces correlate with these trends. Calculated DLVO energy profiles predict much greater sensitivity to changing solution chemistry. Sticking efficiencies derived from AFM measurements range from 9.6 × 10-17 to 1 in solutions of low ionic strength (IS) and from 2.6 × 10-33 to 1 at higher IS. Corresponding α values determined from DLVO theory are essentially zero in all tested solutions. Sticking efficiencies calculated in this study are smaller than values determined from column and field studies in similar systems; however, α derived from AFM data and the IFBL model more closely represent field data than do values calculated from DLVO energy values. A comparison with different methods of calculating α suggests that reversible adhesion may be significant in column-scale transport studies. Copyright © 2005 Elsevier Ltd.
Keywords: Enterococcus faecalis